Peningkatan Kualitas Pembelajaran Sekolah Dasar melalui Pengelolaan Kurikulum - Istianah Nur Wulandari; Oktavia Kusuma D.H; Rahma Salsabila; Lisa Virdinarti Putra; Yunioresa Izak Umang (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Education is a fundamental pillar in the development of a sustainable society, where the curriculum serves as a guide in the learning process. This article discusses the importance of effective curriculum management to enhance the quality of classroom learning, particularly in the context of the Merdeka Curriculum in Indonesia. Through a literature study method, this research identifies strategic steps necessary for improving the quality of learning in schools, including analyzing student needs, developing technology-based teaching materials, and providing ongoing training for teachers. The theory of George R. Terry on POAC (Planning, Organizing, Actuating, Controlling) is adopted as a framework for planning, organizing, implementing, and controlling the curriculum process. The research findings indicate that systematic and collaborative curriculum management can increase student engagement, facilitate more dynamic learning, and create a learning environment that is responsive to student needs. Therefore, effective curriculum management not only focuses on academic achievement but also on the development of students' social, emotional, and character skills, which are essential for forming a generation ready to face global challenges.